Nutritional and socio-economic determinants of cognitive function and educational achievement of Aboriginal schoolchildren in rural Malaysia - Al-Mekhlafi, H.M.; Mahdy, M.A.; Sallam, A.A.; Ariffin, W.A.; Al-Mekhlafi, A.M.; Amran, A.A.; Surin, Johari (Cambridge University Press, 2011)
A community-based cross-sectional study was carried out among Aboriginal schoolchildren aged 7-12 years living in remote areas in Pos Betau, Pahang, Malaysia to investigate the potential determinants influencing the cognitive function and educational achievement of these children. Cognitive function was measured by intelligence quotient (IQ), while examination scores of selected school subjects were used in assessing educational achievement. Blood samples were collected to assess serum Fe status. All children were screened for soil-transmitted helminthes. Demographic and socio-economic data were collected using pre-tested questionnaires. Almost two-thirds (67.6 ) of the subjects had poor IQ and most of them (72.6) had insufficient educational achievement. Output of the stepwise multiple regression model showed that poor IQ was significantly associated with low household income which contributed the most to the regression variance (r(2) 0.059; P=0.020). Low maternal education was also identified as a significant predictor of low IQ scores (r(2) 0.042; P=0.043). With educational achievement, Fe-deficiency anaemia (IDA) was the only variable to show significant association (r(2) 0.025; P=0.015). In conclusion, the cognitive function and educational achievement of Aboriginal schoolchildren are poor and influenced by household income, maternal education and IDA. Thus, effective and integrated measures to improve the nutritional and socio-economic status of rural children would have a pronounced positive effect on their education.